+0  
 
+1
15
1
avatar+344 

 

smileysmileysmiley

qualitystreet  May 17, 2018
Sort: 

1+0 Answers

 #1
avatar+86568 
+2

a)   f(2)  = [ 2 + 3 ] /2  =  5/2

 

b)  for f(x), write y

 

y  = [ x + 3 ] / 2     multiply both sides by 2

 

2y  = x +  3     subtract 3 from both sides

 

2y  - 3  = x        "swap" x and y

 

2x - 3  =  y   =  f-1(x)

 

c)  f-1 (12) =    2(12)  - 3   =  24  - 3     =      21

 

 

 

 

cool cool cool

 
CPhill  May 17, 2018

23 Online Users

avatar
avatar
avatar
avatar
New Privacy Policy (May 2018)
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  Privacy Policy